Faktor Risiko yang Berhubungan dengan Kejadian Penyakit Mioma Uteri - Ivani Laning; Imelda Manurung; Amelia Sir (Lontar : Journal of Community Health, 2019)
Uterine myoma is a benign tumor of the uterine muscle, accompanied by connective tissue so that it can be in solid form, because the connective tissue is dominant and soft. The incidence of uterine myoma in Indonesia at 2013 showed found 2,39 % - 11,70% in all gynecological cases suffererswhich generally occur in women age > 35 years. This study aims to determine the risk factors associated with the incidence of uterine myoma in patients at RSUD Prof. Dr. W.Z. JOHANNES kupang in 2019. This type of research is observational analytic with a case control design. The number of samples were 41 respondents who suffered from uterine myoma and 41 respondents who did not suffer from uterine myoma, who were randomly selected and total sampling with a level of confidence α = 0.05. Each variable examined was tested using the chi-square test to find out the relationship of risk factors for the occurrence of uterine myoma. The results showed parity variables, (p = 0.014, OR = 4.132, and 95% CI = 1.423-11.996), age of menarche (p = 0.001, OR = 5,624, and 95% CI = 2,030-15,583) and family history (p = 0.008, OR = 4,565, and 95% CI = 1,577-13,219) had a relationship with the incidence of uterine myoma, while the old variables were the use of hormonal contraception (p = 0.816, OR = 0.805, and 95% CI = 0.322-2.009) and obesity (p = 0.312, OR = 1,915, and 95% CI = 0.694-5,282) had no association with the incidence of uterine myoma. Advice for nulliparous women to carry out routine cheks on medical personnel for preventive measures and early diagnosis as well as women who experience early menstruation to check their reproductive organs if there are menstrual complaints or menstruation in order to establish an early diagnosis of myoma uteri.